Catalyst development for the direct arylation of aryl chlorides, bromides and iodides - Parisien, Mathieu (University of Ottawa (Canada), 2006)
Tricyclic biaryls were formed by a direct arylation reaction conducted in the presence of catalytic amounts of Pd(OAc)2 and tricyclohexylphosphine. Aryl chlorides, bromides and iodides could all be used and the methodology was applied to the synthesis of 6H-benzo[c]chomenes; 9, 10-dihydrophenanthenes; 5, 6-dihydrophenanthridines (if the nitrogen atom was protected) with yields ranging between 79% - >99%. Fluorene, dibenzofurans and carbazoles (unprotected NH) could also be formed in high yields (81%- 99%) using this technique. It has been found that both electronic and steric factors influence the regioselectivity of the reaction. Furthermore, mechanistic investigations have been conducted to establish which one of four possible pathways is taking place. The results of these experiments point towards either a sigma-bond metathesis or an SE3 palladation. The methodology described above was applied to the synthesis of natural products. (Abstract shortened by UMI.)
Keywords: Chemistry, Organic.